Efectos de la semilla de linaza (Linum usitatissimum L) como reemplazante parcial de semilla y aceite de soya en dietas de pavo sobre el crecimiento, rendimiento de carcasa, parámetros hematológicos y metabolitos lipídicos - Paredes, Manuel (2022)
The study aimed to determine the effect of flaxseed in the diet of fattening turkeys on growth, carcass performance, haematological parameters and lipid metabolites. In total, 160 male Hybrid Converter turkeys of 42 days of age and body weight of 2.41 + 0.13 kg were randomly distributed in 4 treatments, each one with 4 repetitions of 10 birds. The turkeys received diets with 0% (control diet), 5, 10 and 15% raw flaxseed without grinding. Turkeys of the 10% treatment, in the phase from 43 to 91 days of age, obtained greater body weight gain and better feed conversion. Turkey carcass yield decreased with 15% flaxseed in the diet; however, the carcass contained less abdominal fat compared to the 0, 5 and 10% treatments. Treatment with 15% reduced serum cholesterol and flaxseed cholesterol at any level (5, 10, and 15%) can reduce serum triglycerides.